PERAN ARSIPARIS DALAM MENGELOLA ARSIP SEBAGAI SUMBER INFORMASI - Khodijah, Khodijah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
Archives have a role as a source of information in organization or individual life. Archives have specific uses for administrative purposes, law, financial, education, research and verification. Archives are divided into dynamic and static. Dynamic archives are needed directly in the planning, implementation of national life in general or used directly in the administration of the State. While the static archive is an archive that is not used directly for planners, administration, national life in general, or for the administration of day-to-day administration of the State. The archivist is a professional who is responsible for managing important archives. An archivist is a person who is trained professionally, experienced, and responsible in the management of the archives by conducting assessment activities and identifying archives continuously, documenting and preserving the archive. The institutional archive should be able to process information as best as possible and keep archive repository because archives are information that do not have duplication or cannot be reproduced.